2015
DOI: 10.1007/s12288-015-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole Induced Total Myeloid Aplasia with Delayed Recovery Despite Granulocyte Colony Stimulating Factor (G-CSF): Marrow Progenitor Recovery Kinetics

Abstract: An eighteen-year-old female with Graves thyrotoxicosis presented with methimazole-induced agranulocytosis and total myeloid aplasia. The bone marrow at presentation showed complete absence of myeloid precursors and striking plasmacytosis. 16 days later, myeloid precursors were still absent morphologically; however bone marrow flow cytometry and cell culture detected an improvement in myelogenesis, which was soon followed by clinical recovery of agranulocytosis. Neutrophil recovery was delayed until day 22 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meanwhile, decitabine assisted in the treatment of MDS by regulating the production of ROS (Wang, Guo, Guo, Zhang, & Ren, 2019a). It has been found that methimazole can interfere with the oxidation of tyrosine groups by inhibiting peroxidase, leading to anemia or granulocyte deficiency, and myeloid aplasia (Sarker et al, 2015; Yang et al, 2013). Methimazole increased dramatically in the MDS group, indicating that methimazole metabolism was affected, and HSCT had a regulatory effect on methylimidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, decitabine assisted in the treatment of MDS by regulating the production of ROS (Wang, Guo, Guo, Zhang, & Ren, 2019a). It has been found that methimazole can interfere with the oxidation of tyrosine groups by inhibiting peroxidase, leading to anemia or granulocyte deficiency, and myeloid aplasia (Sarker et al, 2015; Yang et al, 2013). Methimazole increased dramatically in the MDS group, indicating that methimazole metabolism was affected, and HSCT had a regulatory effect on methylimidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow examination showed that the M:E ratio was <0.5. Hence, bone marrow recovery from agranulocytosis after G-CSF treatment was delayed (40). Furthermore, the older the patients, the less active the bone marrow.…”
Section: Discussionmentioning
confidence: 99%